2015
DOI: 10.1038/nature14403
|View full text |Cite
|
Sign up to set email alerts
|

A model of breast cancer heterogeneity reveals vascular mimicry as a driver of metastasis

Abstract: Cancer metastasis requires that primary tumour cells evolve the capacity to intravasate into the lymphatic system or vasculature, and extravasate into and colonize secondary sites1. Others have demonstrated that individual cells within complex populations show heterogeneity in their capacity to form secondary lesions2–5. Here we develop a polyclonal mouse model of breast tumour heterogeneity, and show that distinct clones within a mixed population display specialization, for example, dominating the primary tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
371
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 362 publications
(390 citation statements)
references
References 23 publications
17
371
0
2
Order By: Relevance
“…Recent studies using a breast metastasis model have shown that SERPINB2 protects metastatic cells from plasminogen activator plasmin in the brain, providing a metastatic advantage (55). Another serpin family member, Serpine2, was initially discovered in a model of breast cancer metastasis to bone and later reported to facilitate tumor cells to form vascular-like networks enabling perfusion and lung metastasis (64,65). Likewise, SERPINE1 has been used as a prognostic marker of breast cancer and evaluated during chemotherapy administration (66,67).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using a breast metastasis model have shown that SERPINB2 protects metastatic cells from plasminogen activator plasmin in the brain, providing a metastatic advantage (55). Another serpin family member, Serpine2, was initially discovered in a model of breast cancer metastasis to bone and later reported to facilitate tumor cells to form vascular-like networks enabling perfusion and lung metastasis (64,65). Likewise, SERPINE1 has been used as a prognostic marker of breast cancer and evaluated during chemotherapy administration (66,67).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is a rare and poorly studied phenomena, cancer cells can transdifferentiate into endothelial cells or pericytes to mimic components of the tumor microenvironment . Vascular mimicry has recently been reported to facilitate metastasis of 4T1 mouse mammary tumor cells (Wagenblast et al 2015). Further research is needed to explore whether transdifferentiation events can also happen at the metastatic site to enable metastasis initiation and whether transdifferentiation is one of the cellular properties of some MICs.…”
Section: Cd44mentioning
confidence: 99%
“…However, recent studies using lineage tracing, barcode sequencing, and whole-genome sequencing are shedding light on this question and have demonstrated a mostly polyclonal nature of metastasis (Fig. 5;McFadden et al 2014;Gundem et al 2015;Maddipati and Stanger 2015;Wagenblast et al 2015).…”
Section: Mic Heterogeneity: Clonal or Polyclonal Metastasismentioning
confidence: 99%
See 2 more Smart Citations